دور العلماء في تربية الجانب الإيماني للخلفاء (Al-Qamar, 2022)
The Islamic scholars to God Almighty have a great role to play in promoting brotherhood among Muslims, eliminating whatever stands in his way and weakens his power. That is because they are the inheritors of the prophets in change and reform, and they are always the bearers of the torch of guidance, and the safety valve for creation from misguidance and destruction, through their efforts of elucidation and communication, advice, and guidance, and taking people’s hands to the straight path of God. They must advise Muslims - rulers and rulers - and to explain to everyone the importance of Islamic brotherhood and its status in the Shariah, to alert them to its danger and necessity, and to explain its effects on the life of the nation, individuals, and societies, and to remind them of everything that would urge them to stick to their brothers and rally around them and warn them against neglecting them. forfeiting her rights. It makes the Muslims one group, standing in front of the eastern bloc, the western bloc, and other blocs that gather in which Islam has no place, and that the Islamic group will be a source of good for humanity as it was in the era of the Prophet, may God bless him and grant him peace, and the era of the adults after him, rather the era of the kings who were ruling Muslims while they are gathered, whether the ruling is as stated in the Qur’an and the Sunnah, or they differed from it in ways that were few or many.
Keywords: Reflection of Dawah